Gender Differences in the Relationship between Living alone and Depressive Symptoms in Elderly Korean Adults - KIM, Young Bum (Iran J Public Health, 2019)
BACKGROUND: This study examined gender differences in the relationship between living alone and depressive symptoms in elderly Korean adults and the variables that influence this relationship. METHODS: We conducted a secondary analysis using fourth-wave data from adults 65 yr of age or older who participated in the Korean Longitudinal Study of Aging. Depressive symptoms were measured using the 10-item short-form of the Center for Epidemiological Studies Depression Scale. Multiple logistic regression analyses were used. RESULTS: After controlling for the factors of formal and informal social activities, financial support from children, employment, activities of daily living, instrumental activities of daily living, self-rated health, frequency of meals, and gender, living alone (AOR=1.45, 95% CI =1.09–1.93, P=0.010) was an independent risk factor that contributed to depressive symptoms in late life. Living alone was more likely to elevate depressive symptoms in older women but not in older men. CONCLUSION: Gender differences in the depressive effect of living alone in late life may differ across diverse cultures.